Level of Dairy Farmers Participation in Extension Program in Enrekang Regency - S. Baba (Jurnal Ilmu dan Teknologi Peternakan, 2012)
One of the reasons for the derease of extension performance in fulfilling farmer needs is the decrease of dairy farmer participation in extension program.  The objective of this study was to identify the level of dairy farmer participation in extension program in Enrekang Regency. The method used was descriptive analysis by comparing participation level of dairy farmer in central area with that in non-central area in terms of planning, implementing and applying the extension program. There were 103 respondents, 57 respondents in central area (55.13%) and 46 respondents (44.87%) in non-central area, respectively were involved in this study. The data were analysed using t student test with independent group.  The result showed that the level of dairy farmer participation in extension planning was moderate in the central area which was lower than that in the non central area. Moreover, dairy farmer participation in the implementation and utilization of extension programs were similar for both groups.  It can be concluded that the level of dairy farmer participation in the extension programs in Enrekang Regency was high.